Formation mechanisms of ZnO nanowires on polycrystalline Au seed layers for piezoelectric applications. (29th May 2019) - Lausecker, Clément; Salem, Bassem; Baillin, Xavier; Roussel, Hervé; Sarigiannidou, Eirini; Bassani, Franck; Appert, Estelle; Labau, Sébastien; Consonni, Vincent
Abstract: ZnO nanowires are considered as attractive building blocks for piezoelectric devices, including nano-generators and stress/strain sensors. However, their integration requires the use of metallic seed layers, on top of which the formation mechanisms of ZnO nanowires by chemical bath deposition are still largely open. In order to tackle that issue, the nucleation and growth mechanisms of ZnO nanowires on top of Au seed layers with a thickness in the range of 5–100 nm are thoroughly investigated. We show that the ZnO nanowires present two different populations of nano-objects with a given morphology. The majority primary population is made of vertically aligned ZnO nanowires, which are heteroepitaxially formed on top of the Au (111) grains. The resulting epitaxial strain is found to be completely relieved at the Au/ZnO interface. In contrast, the minority secondary population is composed of ZnO nanowires with a significant mean tilt angle around 20° with respect to the normal to the substrate surface, which are presumably formed on the (211) facets of the Au (111) grains. The elongation of ZnO nanowires is further found to be limited by the surface reaction at the c -plane top facet in the investigated conditions. By implementing the selective area growth using electron beam lithography, the position of ZnO nanowires is controlled, but the two populations still co-exist in the ensemble. These findings provide an in-depth understanding of the formation mechanisms of ZnO nanowires on metallic seed layers, which should be taken into account for their more efficient integration into piezoelectric devices.